Wilms tumor in childhood: Single centre retrospective study from the National Institute of Oncology of Rabat and literature review - Fadoua Rais; Naoual Benhmidou; Ghizlane Rais; Hasnaa Loughlimi; Fadila Kouhen; Abdelhak Maghous; Jihane Aarab; Khadija Bellahammou; Mouna Moukinebillah; Mohamed Khattab; Sanaa Chala; Sanaa Elmejjaoui; et al. (Elsevier, 2016)
Background: Wilms tumor is a very common renal malignancy in children. Prognosis has been improved dramatically during the last few decades because of multimodal treatment and successful sequential studies. Through a retrospective study conducted in the National Institute of Oncology of Rabat, concerning children with Wilms tumor treated following the International Society of Pediatric Oncology protocol (93-01) between 2005 and 2010, we report the experience of our institute in treatment of this malignancy. We analyze also the clinicopathologic and therapeutic aspects impacting the outcome results and compared to literature data. Results: Fifty-two patients with Wilms tumor treated in the department of radiotherapy after receiving chemotherapy and surgery at the department of hemato-oncology in children hospital of Rabat were enrolled. The main characteristic was the high prevalence of locally advanced and metastatic stages (32.6% of stage IV). With a median follow up of 54.8 months [20-79], we observed a complete response in 32 cases (61.5%), local recurrence in only one case (1.9%), metastatic relapse in 3 cases (5.8%), both local and metastatic recurrence in 3 cases (5.8%) and disease progression in 8 cases (15.4%). The mean duration of overall survival was 91.2 months. The estimated 2-year and 5-year overall survival were 78.7% and 70.1% and for metastatic patients 68.8% and 62.5% respectively. At univariate analysis several parameters were tested for survival, but only age, anaplasia, lymph node involvement, type of metastasis and response to treatment were found to significantly impact the overall survival. Outcome was better for localized tumors (stage I, II and III) compared with disseminated tumors (stage IV and V) combined. Also a better survival rate was found in the low and intermediate risk group compared to high risk, but not statistically significant. Conclusion: The relatively low outcome found in this series compared to literature can be mainly explained by the higher prevalence of metastatic disease compared to other series, but also by diagnosis and therapeutic delay, more likely because of bad socioeconomic conditions and lack of coordination between different operators. However, our results are nevertheless comparable to maghrebian series. Our department has established many procedures for improving the outcome and further studies are necessary to evaluate their efficiency.